Matematyka

Autorzy:Karolina Wej, Wojciech Babiański, Ewa Szmytkiewicz, Jerzy Janowicz

Wydawnictwo:Nowa Era

Rok wydania:2016

Zapisz w prostszej postaci. a) 5√2+√2 b) 9√10-4√10-2√10 4.5 gwiazdek na podstawie 6 opinii
  1. Gimnazjum
  2. 2 Klasa
  3. Matematyka

Zapisz w prostszej postaci. a) 5√2+√2 b) 9√10-4√10-2√10

5
 Zadanie

6
 Zadanie

`a) \ \ 5sqrt2+sqrt2=6sqrt2` 

`b) \ \ 9sqrt10-4sqrt10-2sqrt10=9sqrt10-6sqrt10=3sqrt10` 

`c) \ \ 6root(3)9-2root(3)9-3=4root(3)9-3` 

`d) \ \ 7root(3)4+2root(3)(-4)=7root(3)4+2*root(3)(-1*4)=7root(3)4+2*(root(3)(-1)*root(3)4)=7root(3)4+2*(-1*root(3)4)=` 

`=7root(3)4+2*(-root(3)4)=7root(3)4-2root(3)4=5root(3)4` 

`e) \ \ sqrt45-sqrt20=sqrt(9*5)-sqrt(4*5)=sqrt9*sqrt5-sqrt4*sqrt5=3sqrt5-2sqrt5=sqrt5` 

`f) \ \ sqrt48+sqrt27=sqrt(16*3)+sqrt(3*9)=sqrt16*sqrt3+sqrt3*sqrt9=4sqrt3+3sqrt3=7sqrt3` 

`g) \ \ root(3)16+root(3)128=root(3)(8*2)+root(3)(64*2)=root(3)8*root(3)2+root(3)64*root(3)2=2root(3)2+4root(3)2=6root(3)2` 

`h) \ \ root(3)375-root(3)24-root(3)(-8)=root(3)(3*125)-root(3)(3*8)-(-2)=root(3)3*root(3)125-root(3)3*root(3)8+2=`

`=5root(3)3-2root(3)3+2=3root(3)3+2` 

`i) \ \ root(3)(-80)+root(3)(-10)=root(3)(-8*10)+root(3)(-1*10)=root(3)(-8)*root(3)10+root(3)(-1)*root(3)10=` 

`=-2root(3)10-1root(3)10=-3root(3)10`